The European Super League debacle: why regulation of corporate football is essential - Welsh, J. (Soccer & Society, 2023)
On 18 April 2021, 12 European football clubs collectively issued a letter of intent to form a new European Super League. This attempted coup was strongly opposed across English football. Afterwards, the responsible owner-oligarchs were singled out for special criticism from pundits and supporter organizations alike. What emerged was a focus upon the personal greed and social indifference of those individuals, but what was less forthcoming in the days following was an analysis capable of putting the `greed thesis` into a more effective social, economic, and even historical context. This article strives for a more sociological understanding of the April 18th coup, to understand better the broader social developments in the political economy of English football from which the coup has come into being. This article calls for regulatory reform of professional football in England, to show why such reform is not merely more plausible now but more necessary.